Inquiry Based Teaching Material Development Guided in Calor and Materials the Transfer of Class V Primary State 2 Alue Teh - Santi Dewi; Fauziah Harahap; Adi Sutopo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Development of Inquiry-Based Teaching Materials Guided by the Material of Heat Transfer Class V Elementary School 2 Alue Teh This study aims to: 1) produce a product in the form of science teaching materials based on guided inquiry on heat transfer material; 2) describe the results of product validation based on guided inquiry teaching materials on the material heat transfer class V Elementary School 2 Alue Teh; and 3) analyzing effectiveness science teaching materials based on guided inquiry on heat transfer material can improve student learning outcomes class V Elementary School 2 Alue Teh. Research This was carried out in class V of Alue Teh 2 Public Elementary School. This research is a Research Research & amp; Development (R & D) includes Define (definition), Design (Design), Develop (development), and Disseminate (deployment). The design of teaching materials uses small group trials and large group trials which was conducted in class V Elementary School 2 Alue 2 Alue Teh. Data has been verified by 2 a material expert lecturer, and 2 design expert lecturers. Overall the results of expert validation the material obtained an average of 92% with the very feasible category while the results the design expert validation as a whole obtained an average of 95% in the category very worthy. At the effectiveness stage, the results showed that the second posttest data on the ability of student learning outcomes has a value of t count (= 0,000) so there is a difference because sig (2-tailed) & lt; 0.05 and t count is positive so that H 0 is rejected. Based on this, it can concluded that "there is a significant difference in learning outcomes among students who are taught using based teaching materials guided inquiry with students who are not taught to use inquiry guided.